1996
DOI: 10.1016/0014-5793(96)00871-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of the essential arginine residues of pyruvate dehydrogenase prevents its phosphorylation by kinase

Abstract: The mechanism of regulatory phosphorylation of the pyruvate dehydrogenase component (El) of muscle pyruvate dehydrogenase complex was studied. Chemical modification of the arginine residues essential for substrate binding was shown to prevent incorporation of 32p from [T-3zP]ATP into E1 catalyzed by kinase and to exclude completely the interaction of holo-E1 with pyruvate. It is proposed that negatively charged phosphoseryl residues may compete with pyruvate for the active site arginine and thereby block the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The partial protection from phosphorylation (inactivation) of the enzyme provided by this analog does not rule out that the phosphorylation and substrate binding sites are close to each other. Competition for the positively charged guanidinium group of the arginine residue, which binds the pyruvate carboxylate [16], may block substrate binding to the active sites of phosphorylated El. …”
Section: Discussionmentioning
confidence: 99%
“…The partial protection from phosphorylation (inactivation) of the enzyme provided by this analog does not rule out that the phosphorylation and substrate binding sites are close to each other. Competition for the positively charged guanidinium group of the arginine residue, which binds the pyruvate carboxylate [16], may block substrate binding to the active sites of phosphorylated El. …”
Section: Discussionmentioning
confidence: 99%
“…The studies on the mechanism of inactivation of mammalian and avian E1s showed the effect of E1 phosphorylation on the affinity for TPP and the formation of enzyme-bound HE=TPP from E1-TPP in either the forward (pyruvate as a substrate) or reverse reaction (acetylhydrolipoate as a substrate) (Roche and Reed, 1972;Walsh et al, 1976;Butler et al, 1977;Nemerya et al, 1996). In a recent study the mechanism of inactivation of human E1 was investigated using site-specific replacement of the three phosphorylation sites (Korotchkina and Patel, 2001a).…”
Section: Mechanism Of Inactivation Of Human E1 By Phosphorylation Of mentioning
confidence: 99%
“…Many chemical modification studies of E1 have been performed. Cysteine [6–8], histidine [7], tryptophan [9, 10], arginine [11, 12]and lysine [13]residues have been suggested to be located in or near the active site, but the role of these residues in the mechanism of E1 is far from clear.…”
Section: Introductionmentioning
confidence: 99%